Explorasi Hubungan Tingkat Pengetahuan dan Sikap Serta Persepsi Pasien Kanker tentang Perawatan Paliatif - Sitorus, Tetty H; Christina, Juliana; Musri, Musri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the relationship between knowledge attitudes and perceptions of cancer patients about palliative care in Bandung. The method used is a mixed methods study. The results of the study showed that the relationship between knowledge and emotions could be known with a p-value of 0.021, knowledge and cognitive/perceptual can be known with a p-value of 0.001, knowledge and behavior can be known with a p-value of 0.044, knowledge and attitude can be known with a p-value of 0.113. The results of the thematic analysis show four themes, namely: understanding palliative care, financial problems, losing hope and expecting support, and expecting prayer. In conclusion, there is no significant relationship between knowledge and attitude. Still, the components of attitude: cognitive/perceptual, emotional, and behavior have a significant relationship with patient knowledge of palliative care. Keywords: Cancer, Knowledge, Palliative Care, Perception, Attitude